2018
DOI: 10.3892/ol.2018.9855
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous endometrioid endometrial and ovarian carcinomas are biologically related: A clinico‑pathological and molecular (next generation sequencing) study of 22�cases

Abstract: The criteria for distinction between independent primary tumors and metastasis from one site to the other in synchronous endometrioid endometrial and ovarian carcinoma (SEO) has been a matter of dispute for a long time. In our study we performed a comprehensive clinico-pathological and molecular analysis of 22 cases of SEO. Based on conventional clinico-pathological criteria the cases were classified as independent primary tumors (10 cases) and metastasis from one location to the other (12 cases). All tumors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Combining our previously published synchronous EC/OC Lynch syndrome case, SV2 [ 12 ], with the analyses performed here, we report a 40% (2/5) rate of independent primary tumors versus metastatic lesions in patients with Lynch syndrome. This is in contrast to sporadic synchronous clinically independent ECs/OCs, which have been consistently shown to be clonally related and metastases from each other, as demonstrated by both our group and others [ 13 16 , 41 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 44%
“…Combining our previously published synchronous EC/OC Lynch syndrome case, SV2 [ 12 ], with the analyses performed here, we report a 40% (2/5) rate of independent primary tumors versus metastatic lesions in patients with Lynch syndrome. This is in contrast to sporadic synchronous clinically independent ECs/OCs, which have been consistently shown to be clonally related and metastases from each other, as demonstrated by both our group and others [ 13 16 , 41 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 44%
“…A total of 265 studies were further assessed by the full-text review, of which 145 studies not meeting the criteria (described in the Methods section and Figure S1 ) were excluded. Finally, for the analysis, we included 123 studies: 120 studies from the PubMed search and 3 hand-searched studies [ 15 , 16 , 18 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsmentioning
confidence: 99%
“…In ovarian tumors the criteria include the the presence of endometriosis, size and laterality of the tumor, surface implants, hilar location, lympho vascular space invasion, and multinodularity. SEOC is ordinarily more likely to be stage I disease with endometrioid histology[6,7]. In the present case we ultimately considered both to be primary carcinomas in the uterus corpus and ovary.…”
Section: Discussionmentioning
confidence: 95%
“…As well as congenital genetic mutations, somatically acquired genetic abnormalities such as punctiform mutations, loss of heterozygosity and microsatellite instability can also contribute to carcinogenesis[2]. Hájková et al[7] conducted comprehensive molecular analysis in 22 SEOC patients and reported that clonal origin was confirmed in all of them by way of at least one shared mutation in PTEN, AKT1, PIK3CA, KRAS, TP53, or ARID1A. Microsatellite instability phenotypes were detected in 5/22 (22.7%) SEOC of the patients.…”
Section: Discussionmentioning
confidence: 99%